Avaliação em saúde bucal na perspectiva do usuário: enfoque ao estudo da acessibilidade organizacional - Castro, Ricardo Dias de (2007)
Due to the fact of oral health sector reestructuration within Brazilian public health politics, this work had the object of evaluating, under users point of view, the accessibility to oral health services in Santa Cruz (RN), focusing on the organizational aspect. To achieve this, questionnaires were given to users in their homes, considering the censitary sector. Nine sectors of the urban zone were evaluated, selected by chance, and one from the rural zone, selected by convenience. The sample was composed by 194 users, calculated considering the estimated prevalence of event represented by the indicator I ve never been to the dentist + I ve been to the dentist more than three years ago from the Projeto SB Brasil Report . To complement the results, interviews were made with others actors involved in the process of oral health care: professionals (dentists) and manager (Health Municipal Secretary). From the data obtained it was possible to identify that 12,9% of the population had never visited the dentist, and that the search for the service was not influenced by the users individual and socioeconomics characteristics, excepting the gender. It was verified that 36,1% of the users went to the dentist in less than one year, with the youngests (p<0,05) being among those who went to the dentist more frequently. 63,3% of the interviewed related that they found some kind of difficulty when they search for dentistry services, with the difficulties for schedule, the queues and the long wait among the most cited. It was identified that 43,2% of the users wait three weeks or more for the appointment. It is still pointed out that 71,4% of the interviewed find difficulties to get urgency appointment, the long wait to be attended by the dentist was the most found. 92,9% and 94,1% of the interviewed had never been headed to especialized appointments and complementary exams, respectively. Due to the data founded, it was possible to verify that the accessibility to oral health services in Santa Cruz (RN) is damaged by factors related to the organization of public polices developed, mainly in relation to the working process